THE THE LEVEL OF KNOWLEDGE AND ATTITUDES OF PHARMACY STUDENTS TOWARDS CORTIOSTEROIDS USES - Tri Budi Julianti (Jurnal Ilmu Kesehatan, 2019)
Corticosteroids are hormones that naturally produced by the human body through the adrenal gland. Cortisone hormones play a role in regulating blood sugar, protein, fat, the body's defense system and bone formation. Corticosteroid drugs are commonly used for anti-inflammatory, pruritic, dermatological, rheumatologic, pulmonary, hematological, ophthalmological, immunological, and gastrointestinal, called glucocorticoids. Long-term therapy with corticosteroids can cause severe side effects if given in high doses. The aim of this study was identification of the level of knowledge and attitude in corticosteroid use, especially in pharmacy students. This type of research was cross-sectional which aims to see the relationship between the dependent variable and the independent variable in Samarinda. This research was conducted in 2019 by conducting a questionnaire survey test using Google Form. Data analysis in the form of bivariate analysis using the Mann-Whitney test with SPSS Statistic 23 software program. Respondents who participated in this research amounted to 118 people with ages ranging from 17 to 25 years. In this research shows that pharmacy students have a fairly good knowledge of corticosteroids with the majority of the percentage of correct answers ≥72%. The results of the analysis obtained p value 0.008 (p <0.005) and obtained r value 2.7. There is a significant influence between knowledge of corticosteroids on their attitude using corticosteroids and showing good knowledge has the potential of 2.7 times to have a good attitude.